Globalisation and the Colonising State of Mind - Jackson, Moana (Resistance: An Indigenous Response to Neoliberalism, 2007)
Resistance: An Indigenous Response to Neoliberalism is a collection of papers from Maori academics, activists and leaders on the connection between global practices of neoliberalism and the diverse forms of Maori resistance that aim to destablize them.Aotearoa is one of the world leaders of neoliberalism. Successive New Zealand governments since 1984 have pursued neoliberal policies with a faith, vehemence and confidence in their success that few other governments appear to possess.At a time when 'capital flows across borders as it has never done before, and multinational companies have bigger budgets than many states have ever had', this book encourages people to look more closely at Maori views as integral and inspiring in a globalizing world.Resistance: An Indigenous Response to Neoliberalism is edited by Maria Bargh. The other contributors are Claire Charters, Moana Jackson, Bridget Robson, Cherryl Smith, Maui Solomon, Alice Te Punga Somerville, Annette Sykes and Teanau Tuiono.
Keywords: colonisation; globalisation; neoliberalism; protest

Tino rangatiratanga : water under the bridge? - Bargh, Maria (He pūkenga kōrero: a journal of Māori studies, 2007)
Argues that Māori have been actively engaged in practising tino rangatiratanga in various forms even since before the Declaration of Independence ...
Keywords: colonisation; constitution; government; international relations; iwi; kaitiakitanga; sovereignty; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; water rights